2021
DOI: 10.5937/jomb0-29341
|View full text |Cite
|
Sign up to set email alerts
|

Role of biochemical markers in the monitoring of COVID-19 patients

Abstract: COVID-19 is an infectious disease caused by the SARS-CoV-2 virus, which has given rise to a global sanitary emergency. The clinical characteristics of COVID-19 are varied and can range from an asymptomatic infection to a mild to severe pneumonia. Recent studies have shown that different laboratory parameters become altered in these patients, and as such are useful as biomarkers to assess the progression of the disease and categorize patients that may present a severe and/or fatal clinical condition. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 78 publications
(102 reference statements)
2
30
1
Order By: Relevance
“…Also, biochemical markers, such as LDH, can be used for monitoring COVID-19 patients and reflect the severity and outcome of the disease. Further, our data demonstrated that biochemical values were different from reference values, which were shown in other studies as well ( Yağcı et al, 2021 ; Huang et al, 2021 ; Letelier et al, 2021 ). The current study also showed that age affected the disease outcome when other influencing conditions were not considered.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Also, biochemical markers, such as LDH, can be used for monitoring COVID-19 patients and reflect the severity and outcome of the disease. Further, our data demonstrated that biochemical values were different from reference values, which were shown in other studies as well ( Yağcı et al, 2021 ; Huang et al, 2021 ; Letelier et al, 2021 ). The current study also showed that age affected the disease outcome when other influencing conditions were not considered.…”
Section: Discussioncontrasting
confidence: 47%
“…As expected, the highest mortality rate was detected in patients ≥60 years old. Indeed, the proportion of dead patients over 60 years old was more than 48.38%, while the overall mortality rate was varied between countries ( Letelier et al, 2021 ). The lowest mortality rate was observed in China in patients aged ≥80 years old (3.1%), and the highest rates were observed in New York State (20.99%) and the United Kingdom (20.8%) ( Letelier et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its easy and quick transmission and interhuman spread, the WHO declared it as a pandemic on March 11, 2020 (1). Recent studies have shown that different biochemical parameters are altered in patients with COVID-19, and some of them are useful as indicators of disease severity (4)(5)(6). Patients can have various forms of the disease, from asymptomatic to acute respiratory distress syndrome (ARDS) and respiratory insufficiency (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Many laboratory parameters such as absolute neutrophilia, thrombocytopenia, hypoalbuminemia, the elevation of liver enzymes, creatinine and nonspecific inflammatory markers such as C-reactive protein (CRP) and Interleukin 6 (IL-6) make it possible to assess the severity of the disease and predict the risk of it evolving toward more serious afflictions such as acute respiratory distress syndrome (ARDS), disseminated intravascular coagulation (DIC) and multiple organ failure (MOF). In addition, lymphopenia, elevated D-dimer, ferritin as well as LDH, CPK and troponin markers are the main predictors for the progression of the disease 7 .…”
Section: Introductionmentioning
confidence: 99%